Happy Math War: Game Edukasi sebagai Media Pembelajaran Peningkat Kemampuan Koneksi Matematis - Nabilah Cahyadewi; Ria Sudiana (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2023)
The purpose of this research is to produce media products for game education (Happy Math War) to improve students’ mathematical connection abilities. This research as potential and problems, data collection, product development, design validation, design revisions, preliminary trials, revisions, wide-scale use trials, and revisions. The research subject were students and mathematics teachers at SMP in Kota Serang. The results of the research obtained showed that the fact of a learning media game education Happy Math War is very valid in terms of media and material, has practical value for teachers, and is very practical from student responses. High media effectiveness with an indicated score-gain of 0,80. Based on these results, the developed learning medium is feasible to use to improve students’ mathematical connection abilities. Keywords: educational games, media, connection capabilities